Theoretical analysis of explosions occurrence in tanks in the presence of dispersed water (air) in the fuel - Orazbaev, Алишер (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
The article describes the processes which involve electrification of dielectric hydrocarbon liquids; reviewed mechanism of the formation of the electrostatic potential on the surface of a liquid hydrocarbon that is loaded into the tank (for example, gasoline) demonstrates the results of calculation of the maximum possible values of electrostatic potential, depending on the composition of suspended particulate potential making particles (water, air bubbles) in the liquid.